Effects of dietary Saccharomyces cerevisiae and β‐glucan on the growth performance, antioxidant capacity and immunity response in Macrobrachium rosenbergii. (6th September 2021) - Han, Bei; Zhang, Xin; Chang, Enhui; Wan, Wenlong; Xu, Jie; Zhao, Chenze; Miao, Shuyan
Abstract: A 60‐d feeding trial was conducted to evaluate the effects of Saccharomyces cerevisiae and β‐glucan on the growth performance, feed utilization and immunity response of Macrobrachium rosenbergii . Prawns (0.19 ± 0.01 g) were fed with the basal diet (group C) or other three experimental diets supplemented with S. cerevisiae (group S), β‐glucan (group G) or their combination (group GS), respectively. Results showed that the growth performance of prawns was significantly promoted in group S and GS ( p < 0.05). Immunostimulants supplementation significantly increased the protease activity and the highest amylase activity was found in group G ( p < 0.05). The highest phagocytic index of prawns was observed in group GS ( p < 0.05), and the respiratory burst activity was significantly improved in group S and GS ( p < 0.05). Furthermore, immunostimulant supplementation significantly increased the gene expression of the antioxidant and antimicrobial enzymes of prawns ( p < 0.05). Immunostimulant supplementation also significantly increased the gene expression of prophenoloxidase, toll‐like receptors, heat shock protein 70 and lectins( p < 0.05). Conclusively, S. cerevisiae and β‐glucan both could be used as potential immunostimulants in prawns farming. Considering the comprehensive effects, their combination was more effective in promoting the growth and immunity of prawns.